Social network of malnourished children and its association with family's food and nutritional security - Luciana Karla do Nascimento Barros; Ana Paula Grotti Clemente; Nassib Bezerra Bueno; Luiz Gonzaga Ribeiro Silva Neto; Isabele Rejane de Oliveira Maranhão Pureza; Revilane Parente de Alencar Britto; Mêllyna Rose Costa Santos; Telma Maria de Menezes Toledo Florêncio (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: evaluate the relationship between family's food and nutrition insecurity (FNI) and the social network of malnourished children. Methods: cross-sectional study with 92 children, included in the economic class D-E. For the analysis of the children's social network, the mothers answered four simple questions. To investigate the FNI, the Brazilian Scale of Food Insecurity was used. The association between variables was analyzed by Poisson regression with robust analysis of variances. Results: 56.5% of the children had a weak social network (<10 individuals), and the prevalence of FNI was 72.8%. An inverse association was observed between children of the daily social network and FNI family (OR=0.94; CI95%=0.89-0.99], p=0.03). The number of individuals in the children's daily social network was negatively associated with the likelihood of FNI. The mother's educational level was also related to FNI (OR=2.20 [CI95%=1.11-4.34]; p=0.02), being the child up to 2.2 times more likely to be in FNI when the mother has less than four years of study. Conclusion: these results suggest that social network is associated with the FNI of malnourished children. Interventions designed to strengthen instrumental and other forms of support among small social networks can improve the health/nutrition of malnourished children with FNI.